2017
DOI: 10.1039/c7cp01994g
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and volumetric sensitivity of the dry sintering process of polymer colloidal crystals: a thermal transport and photonic bandgap study

Abstract: We introduce the in situ characterization of the dry sintering process of face-centred cubic colloidal crystals by two complementary techniques: thermal transport and photonic stopband characterization.Therefore, we employed time-dependent, isothermal laser flash analysis and specular reflectivity experiments close to the glass transition temperature of the colloidal crystal. Both methods yield distinctly different time constants of the film formation process. This discrepancy can be attributed to a volume-(ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Due to the sudden thickness drop above T g , the thermal conductivity increases to around 150 mW m −1 K −1 , which is retained in the following cooling cycle from T g to 25 °C. Similar results are observed from the PMMA colloidal crystals as illustrated in Figure 3b, [47] the thermal conductivity experiences a step-like, irreversible increase from around 120 to ≈200 mW m −1 K −1 at the transition temperature (around 74 °C). It is observed that the initial contact points between colloidal particles are enlarged after reaching the transition temperature (Figure 3c), which reduces the thermal interfacial resistance and leads to a remarkable increase to their thermal conductivity, e.g., up to ≈200% increase.…”
Section: Polymer Colloidal Crystals and Assembliessupporting
confidence: 85%
“…Due to the sudden thickness drop above T g , the thermal conductivity increases to around 150 mW m −1 K −1 , which is retained in the following cooling cycle from T g to 25 °C. Similar results are observed from the PMMA colloidal crystals as illustrated in Figure 3b, [47] the thermal conductivity experiences a step-like, irreversible increase from around 120 to ≈200 mW m −1 K −1 at the transition temperature (around 74 °C). It is observed that the initial contact points between colloidal particles are enlarged after reaching the transition temperature (Figure 3c), which reduces the thermal interfacial resistance and leads to a remarkable increase to their thermal conductivity, e.g., up to ≈200% increase.…”
Section: Polymer Colloidal Crystals and Assembliessupporting
confidence: 85%
“…At this point, the interparticle contact points enlarge and the porosity within the sample vanishes, resulting in a strongly increased thermal conductivity. The kinetics of this transition have been examined elsewhere ( 36 ). In all cases, a sharp increase in thermal conductivity by at least 200% could be programmed to a specific temperature, simply by controlling the second-order phase transition of the constituting polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the optical properties are well known for colloidal crystals, the thermal properties are far from being fully understood . Recent contributions in this field are investigations on nanocrystal arrays, inverse opals, organoclay nanolaminates, and colloidal nanoparticle assemblies …”
Section: Introductionmentioning
confidence: 94%